Case Report: Autoimmune Hemolysis Anemia After Dihydroartemisinin and Piperaquine for Uncomplicated Plasmodium falciparum Malaria - Louvois, Marion; Simon, Loïc; Pomares, Christelle; Jeandel, Pierre-Yves; Demonchy, Elisa; Carles, Michel; Delaunay, Pascal; Courjon, Johan (Frontiers in Medicine, 2022)
Malaria is still an endemic disease in Africa with many imported cases in Europe. The standard treatment is intravenous artesunate for severe malaria and oral artemisinin-based combination therapy (ACT) for uncomplicated malaria. Delayed hemolytic anemia (DHA) after intravenous artesunate has been extensively described and guidelines recommend a biological monitoring until one month after the end of the treatment. The link with an autoimmune process is still unsure. Nevertheless, cases with positive direct antiglobulin test (DAT) have been reported. Conversely, DHA is not recognized as an adverse effect of oral ACT. Previously, only few cases of DHA occurring after oral ACT without intravenous artesunate administration have been reported. We report the case of a 42-year-old man returning from Togo. He was treated with dihydroartemisinin / piperaquine combination for an uncomplicated Plasmodium falciparum malaria, with low parasitemia. Nine days after the end of the treatment he developed hemolytic anemia with positive DAT. Eventually, the patient recovered after corticotherapy. After excluding common causes of autoimmune hemolytic anemia, we considered that dihydroartemisinin / piperaquine treatment was involved in this side effect.